Evictions, migrations and epidemiology in Gokwe during the colonial era - Mudzimu, Asa (Rhodes University, Faculty of Humanities, Department of History, 2017)
Gokwe, being infested with tsetse and mosquito was seen as a 'diseased' environment by the Europeans. Thus, colonial anti-disease campaigns were introduced during the first decade of the 20th century. Initially, the campaigns sought to address economic challenges in the colony as they involved African relocations for the benefit of the Europeans. However, this study argues that these anti-disease campaigns were modified with time and space. The key thrust of the paper is to examine the imbrication between evictions, migrations and disease control in the context of colonial public health system. Apartfrom examining the development of Western medical practices in Gokwe the dissertation explores how this colonial public health system coalesced or clashed with African worldviews. Gokwe matters as a 'frontier' society in many senses. Given colonial efforts to occupy Gokwe and the influx of new evictees and migrants in the 1960s, the study depicts Gokwe as a frontier. The study sees evictions and displacements as programmes tailored to arrest tsetse and the associated diseases in the Zambezi Valley.
Keywords: Uncatalogued